The Influence Of Current Ratio And Return On Assets On Stock Price In Coal Mining Sector Companies Listed On The Indonesian Stock Exchange - Nur Suka Nengsih; Anwar; Nurman; Anwar Ramli; Annisa Paramaswary Aslam (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study aims to analyze the effect of Current Ratio (CR) and Return on Assets (ROA) on stock prices in coal mining companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The background of this study is driven by fluctuations in current ratio, return on assets, and stock prices in the coal industry that indicate a mismatch between financial performance and market valuation. This study uses a quantitative approach with a multiple linear regression method through the assistence of the SPSS application, while the sample is determined by a purposive sampling technique in 18 (eighteen) companies over 5(five) years of observation, resulting in 90 (ninety) observations. The results of the partial test (t-test) show that Current Ratio (CR) has a positive and significant effect on stock prices, indicating that a high level of liquidity provides a positive signal to investors regarding the company's short-term financial stability. Conversely, Return on Assets (ROA) has a negative but insignificant effect on stock prices, indicating that profitability has not been a major factor in influencing investor perceptions in this sector, possibly due to fluctuations in commodity prices and unstable profits. The results of the simultaneous test (F-test) show that CR and ROA together have a significant effect on stock prices, with a coefficient of determination (R²) of 18.8%, meaning that these two variables explain some of the variation in stock prices, while the rest is influenced by external factors such as macroeconomic conditions and global coal prices. This finding supports Signaling Theory (Spence, 1973), which states that financial ratios act as signals for investors in assessing company performance. This study provides an empirical contribution to understanding the determinants of stock prices in the Indonesian mining sector and provides practical implications for management and investors to strengthen liquidity management and increase market confidence.